PERENCANAAN PEMBANGUNAN PENGEMBANGAN PARIWISATA DENGAN BASIS ECOTOURISM SEBUAH KAJIAN PUSTAKA TERSTRUKTUR - Priyanda Kevin Prasetyo; Salahudin Salahudin (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
This study aims to understand how the development planning process in tourism development is based on ecotourism by using the Literature Review method, which is a method of reviewing the main points of thought on the same topic or discussion as an effort to add arguments and author opinions on the topic to be discussed. Based on the results of this research, it is revealed that development planning in tourism development on the basis of ecotourism does not only focus on tourism development on a natural basis, but also provides benefits to the surrounding community, namely as a form of rural development that aims to improve the local economy, where the local community has the main control in tourism development based on this ecotourism. Keywords : Development planning, Tourism, Ecotourism, local communities, economy